Drinking water behavior and willingness to use filters by middle-aged and elderly residents in rural areas: A cross-sectional study in Tengchong, China - Duan, Yuxin; Wu, Ruiheng; Ji, Haoqiang; Chen, Xu; Xu, Jia; Chen, Yunting; Sun, Meng; Pan, Yuanping; Zhou, Ling (Frontiers in Public Health, 2022)
Access to safe drinking water is critical to health and development issues, and residents' drinking behaviour reflects their awareness of health and water hygiene. A questionnaire was conducted to assess drinking water behavior, sanitation and perceptions of drinking water among middle-aged and elderly residents in Tengchong, southwest Yunnan. Two binary logistic regression analyses were conducted to investigate the influencing factors of drinking unboiled tap water and willingness to use filters. Results show that 35% of residents were drinking unboiled tap water, and 29.8% of respondents indicated a willingness to use filters. The model results showed a strong correlation between age, the way of drinking water, having kidney stones, wanting to gain knowledge about drinking water and drinking unboiled tap water (p<0.05). Age, education status, household water treatment (HWT), water storage and willingness to use filters were correlated (p<0.05). Residents' perception of drinking water can reflect residents' drinking water behavior and willingness to a certain extent. Perceived health risks (PHR) and water authority satisfaction (WAT) play an important role (p<0.05) in the model. Government and centres for disease control should strengthen relevant measures such as knowledge popularization and health education, and regulate the water use behavior of middle-aged and elderly residents. Promote safe, economical, and effective household water filtration facilities to ensure public health safety.